Characterization of potentially pathogenic Escherichia coli isolated from chicken farms in Malaysia - Roslee, Roseliza (2019)
Escherichia coli is a part of normal floral in intestinal tract in various animal species. E. coli always considered as non - pathogenic, however certain E. coli strain can cause infection when they harbour certain virulent properties. In poultry, E. coli is the most predominant and important strains affecting poultry industry due to the significant economic loss as result of high mortality and morbidity. This study was conducted to determine the phenotype and genotype characteristic of 125 E. coli isolates available in Veterinary Research Institute (VRI) which are isolated from chicken farms with significant clinical signs and abundant growth upon isolation on growth medium. There was no concrete information regarding E. coli isolated from chicken available elsewhere in the country. This study showed that E. coli isolates recovered from chicken farms were found to have diverse biochemical properties, with no single features was specific for E. coli identification. All the isolates were further categorized into 12 distinct groups based on their biochemical profiles including haemolysis morphology. Serotyping of the E. coli isolates revealed that 69.6% (87/125) isolates in this study cannot be assigned to any serogroups tested. Other serotypes identified were 14.4% O1:K1 (18/125), 10.4% O78:K8O (13/125) and 5.6% O2:K1(7/125) Phylogenetic analysis demonstrated that most of the E. coli isolated from chicken farms in this study belonged to group B1 (36.0%) and group D (28.0%), which is associated with non- virulent strain. Multiplex PCR analysis demonstrated that the most prevalent virulence genes identified were iss 52.0% (65/125), followed by iucD 36.0% (45/125) tsh 32.0% (40/125), vat 14.4% (18/125), astA 12.0%(15/125), papC 12.0% (15/125), irp2 9.6% (12/125), and the least is cva/cvi gene (0%). None of the isolates harbored more than four virulence genes. Further analysis showed that presence of virulence genes among the isolates were highly diverse regardless their biochemical profiles, serotype and phylogenetic groups. Antibiogram analysis revealed that 81.6% (102/125) of the E. coli isolates showed multidrug resistant profiles to different antibiotics. Most of the E. coli isolates were highly resistant to erythromycin 52.8% (66/125), followed with tetracycline 52.0% (65/125), streptomycin 40.0% (50/125), spectinomycin 39.2% (49/125), trimethoprim 38.4% (48/125) and flumequin 37.6% (47/125).These findings also demonstrated that most of the isolates were susceptible to antibiotics commonly used for E. coli infections treatment in poultry with lowest resistant score against polymyxin B (92.8%) and colistin (92.0%). There is no association with the multidrug resistant profiles of the isolates with serotypes, phylogenetic groups and virulence genes profiles observed in this study. Macrorestriction analysis of selected E. coli isolates resulted in heterogenous Pulse Field Gel Electrophoresis (PFGE) pattern. Construction of cluster dendogram of 56 isolates with 60% coeffiecient similarity showed 41 genotypes consists of various serotypes with different biochemical profiles, serotypes, phylogroups and virulence genes profiles. This finding indicate that E. coli isolated from chicken farms in the country derived from different clones which display heterogenous profiles including antimicrobial resistant profiles. In conclusion, this study suggested that E. coli strain isolated from chicken farms was potentially pathogenic with highly diverse phenotype and genotypes. They potentially can cause disease in chicken even though initially they are harmless normal floral in gut as they able to inherit virulence genes from other bacterial strains in gut which enable them to cause disease.